Establecimiento de una plantación de nueve especies forestales con fines de rehabilitación de suelos degradados en la hacienda la Florencia en el cantón y provincia de Loja - Jiménez Cueva, Thalia Paola (2023)
In addition to rehabilitation of degraded soils, forest plantations can contribute to soil retention and conservation, as they become a source of organic matter over time and generate ecological goods and services. One of the causes of soil degradation is overgrazing, intensive agriculture and the use of sloping areas for anthropic activities. In this context, the aim is to rehabilitate the degraded soil on the La Florencia farm. A method known as Miyawaki entails planting species very closely together, causing competition, and accelerating their growth. The system was accompanied by contour lines in its design. The evaluation of survival was based on the relationship between the number of plants established and the number of live plants found at the time of measurement. To evaluate the growth of dasymetric variables, three measurements were made in six months. The average and current six-monthly increase in height and basal diameter was calculated from the differences between height and basal diameter, and an analysis of variance was made from these data. As a result, 627 seedlings of nine species were planted in an area of 2,04 ha at a spacing of 2,5 x 5 m following the contour lines, the average survival of the plantation was 95,69%, the species with the greatest average increase in total height, six months after planting was Alnus acuminata with 37,30 cm; in basal diameter the species with the greatest average increase was Erythrina edulis with 7,89 mm: The analysis of variance showed that there were significant differences in the growth of all the species. Key words: Miyawaki method, contour planting, survival, current six-month increment, mean six-month increment, forest plantation.